Interventional magnetic resonance imaging for guiding gene and cell transfer in the heart. Issue 1 (15th December 2003) - Barbash, I M; Leor, J; Feinberg, M S; Tessone, A; Aboulafia-Etzion, S; Orenstein, A; Ruiz-Cabello, J; Cohen, J S; Mardor, Y
Abstract : Background: Interventional magnetic resonance imaging (iMRI) has the potential for guiding interventional cardiac procedures in real time. Objectives: To test the feasibility of iMRI guided gene and cell transfer to the heart and to monitor myocardial remodelling after myocardial infarction in a rat model. Methods: The MRI contrast agent GdDTPA, together with either Evans blue dye, or a recombinant adenovirus encoding the LacZ gene, or primary fibroblasts tagged by BrdU, were injected into the myocardium of rats under iMRI guidance. Rats were killed seven days after the injection and the hearts sectioned to identify the blue dye, LacZ expression, or fibroblast presence, respectively. In a parallel study, left ventricular area was measured before and after myocardial infarction and in sham operated rats by T1 weighted MRI and by echocardiography. Results: Location of GdDTPA enhancement observed with iMRI at the time of injection was correlated with Evans blue stain, β-gal expression, and the primary fibroblast location in histological studies. iMRI and echocardiography measured a comparable increase in left ventricular area at seven and 30 days after myocardial infarction. A good correlation was found between the iMRI and echocardiographic assessment of left ventricular area ( r  =  0.70; p < 0.0001) and change in left ventricular area with time ( r  =  0.75; p < 0.0001). Conclusions: The results show the feasibility and efficiency of iMRI guided intramyocardial injections, and the ability to monitor heart remodelling using iMRI. Genes, proteins, or cells for tissue engineering could be injected accurately into the myocardial scar under iMRI guidance.